1976
DOI: 10.1042/cs051259s
|View full text |Cite
|
Sign up to set email alerts
|

Renal Urinary Kallikrein in Normotensive and Hypertensive Rats during Enhanced Excretion of Water and Electrolytes

Abstract: 1. Urinary kallikrein excreted by normal rats is significantly increased (P <0.001) 2 h after: (a) water loading, (b) water loading plus frusemide, 0.27 mmol (10 mg) per rat, (c) salt loading. In water-loaded rats, 5 i.u. of renin strikingly reduced kallikrein excretion (P < 0.01) but considerably increased sodium excretion (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

1976
1976
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 7 publications
2
13
1
Order By: Relevance
“…Anti-bradykinin antiserum (which should also bind kallidin) decreased sodium excretion after saline infusion by 50% in rats (MarinGrez, 1974), suggesting that kinin release within the kidney is a cause of the natriuresis of volume expansion. Consistent with this view are reports that kallikrein excretion varies directly with dietary salt in man (Adetuyibi and Mills, 1972), and increases during saline infusion in dogs (DeBono and Mills, 1974) and rats (Croxatto et al, 1975;Croxatto et al, 1976;Godon and Damas, 1974). However, other investigators have found an inverse relation between dietary salt and kallikrein excretion in man , Margolius et al, 1974a) and rats (Johnston et al, 1976a;Johnston et al, 1976b) and reported that saline infusion has no effect on kallikrein excretion in man , Margolius et al, 1974a.…”
Section: Physiological Rolesupporting
confidence: 59%
See 2 more Smart Citations
“…Anti-bradykinin antiserum (which should also bind kallidin) decreased sodium excretion after saline infusion by 50% in rats (MarinGrez, 1974), suggesting that kinin release within the kidney is a cause of the natriuresis of volume expansion. Consistent with this view are reports that kallikrein excretion varies directly with dietary salt in man (Adetuyibi and Mills, 1972), and increases during saline infusion in dogs (DeBono and Mills, 1974) and rats (Croxatto et al, 1975;Croxatto et al, 1976;Godon and Damas, 1974). However, other investigators have found an inverse relation between dietary salt and kallikrein excretion in man , Margolius et al, 1974a) and rats (Johnston et al, 1976a;Johnston et al, 1976b) and reported that saline infusion has no effect on kallikrein excretion in man , Margolius et al, 1974a.…”
Section: Physiological Rolesupporting
confidence: 59%
“…On one observation there is unanimity: kallikrein excretion increases during the action of diuretics (Croxatto et al, 1973;Croxatto et al, 1975;Croxatto et al, 1976;Johnston et al, 1976aJohnston et al, , 1976bNielsen and Arrigoni-Martelli, 1977;Neilsen et al, 1976;Olsen, 1977;Olsen and Ahnfelt-R0nne, 1976) in both dogs and rats. Furosemide and bumetanide, which act on the loop of Henle, thiazides, which act on the distal tubule, and acetazolamide, which acts proximally, are all effective, so the increase in kallikrein excretion probably is not a direct pharmacological action.…”
Section: Physiological Rolementioning
confidence: 99%
See 1 more Smart Citation
“…Solid triangles represent seven puppies studied before the administration of saline or substance P. Open circles represent these puppies during saline loading. Four puppies then received substance P infusion (10 ng. kg-Ismin-') during continued saline loading, solid circles, whereas three puppies continued to receive saline alone, &lid squares.…”
Section: Resultsmentioning
confidence: 99%
“…Kallikrein excretion increased during saline infusion in dogs and rats. 35 - 38 Saline infusion had no effect on kallikrein excretion in humans. 1617 Kallikrein excretion was increased by water-loading in reports of studies in humans 17 and animals, 28293738 but not in other reports.…”
Section: Discussionmentioning
confidence: 99%